Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1128/ec.4.8.1317-1327.2005
|View full text |Cite
|
Sign up to set email alerts
|

Mating Type Loci of Sporisorium reilianum : Novel Pattern with Three a and Multiple b Specificities

Abstract: Sporisorium reilianum and Ustilago maydis are two closely related smut fungi, which both infect maize but differ fundamentally in their mode of plant invasion and site of symptom development. As a prelude to studying the molecular basis of these differences, we have characterized the mating type loci of S. reilianum. S. reilianum has two unlinked mating type loci, a and b. Genes in both loci and adjacent regions show a high degree of synteny to the corresponding genes of U. maydis. The b locus occurs in at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
96
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(104 citation statements)
references
References 63 publications
(50 reference statements)
2
96
0
3
Order By: Relevance
“…Second, within the same strain, pheromone precursor genes code for identical peptides, suggesting the presence of only one MAT specificity per strain. This organization contrasts, for example, with the triallelic P/R locus of several smut species in the Ustilaginales, in which two different MAT-specific pheromones are encoded at each P/R allele (Schirawski et al 2005;Kellner et al 2011). It also differs from other model species in the subphylum Agaricomycotina, such as Schizophyllum commune and C. cinerea, in that these species have evolved an enormous repertoire of pheromone/receptor alleles likely arising by duplication of an archetypal P/R locus, followed by rounds of recombination and diversification between alleles (Riquelme et al 2005).…”
Section: Resultsmentioning
confidence: 83%
“…Second, within the same strain, pheromone precursor genes code for identical peptides, suggesting the presence of only one MAT specificity per strain. This organization contrasts, for example, with the triallelic P/R locus of several smut species in the Ustilaginales, in which two different MAT-specific pheromones are encoded at each P/R allele (Schirawski et al 2005;Kellner et al 2011). It also differs from other model species in the subphylum Agaricomycotina, such as Schizophyllum commune and C. cinerea, in that these species have evolved an enormous repertoire of pheromone/receptor alleles likely arising by duplication of an archetypal P/R locus, followed by rounds of recombination and diversification between alleles (Riquelme et al 2005).…”
Section: Resultsmentioning
confidence: 83%
“…The genetic material within and around these loci shows a high degree of synteny with U. maydis (Schirawski, Heinze, Wagenknecht, & Kahmann, 2005). The b locus exists in at least five different alleles and encodes two subunits of a heterodimeric homeodomain transcription factor (Schirawski et al, 2005). In contrast to U. maydis which has only two alleles, the a locus of S.…”
Section: Sporisorium Reilianummentioning
confidence: 99%
“…Like some other closely related smuts, the mating type locus is composed of two unlinked genomic regions, a and b, which code for a pheromone and pheromone receptor and homeodomain proteins, respectively. The genetic material within and around these loci shows a high degree of synteny with U. maydis (Schirawski, Heinze, Wagenknecht, & Kahmann, 2005). The b locus exists in at least five different alleles and encodes two subunits of a heterodimeric homeodomain transcription factor (Schirawski et al, 2005).…”
Section: Sporisorium Reilianummentioning
confidence: 99%
See 1 more Smart Citation
“…The a-locus has two idomorphs, a1 and a2, that both contain genes encoding a secreted mating pheromone a (mfa1/2) and a G protein-coupled pheromone receptor (pra1/2) used in self, non-self recognition. The a1 locus also encodes Right Border a protein 1 (Rba1) which is thought to target to mitochondrial membrane and the a2 locus encodes two mitochondrial proteins Lga2 and Rga2, as well as a pseudogene rba2 (Schirawski et al, 2005). Studies focusing on the lga2 and rga2 genes from the a locus have demonstrated their involvement in determining mitochondrial inheritance in daughter cells (Brefort et al, 2009).…”
Section: Mating Types In Ustilago Maydismentioning
confidence: 99%